Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Aktivitas Belajar Siswa Materi Keanekaragaman Hayati di Kelas X SMA Negeri 1 Luwuk - Sryfaida Lama'u; Nurlia Nurlia; Sulasmi Anggo (Jurnal Biologi Babasal, 2022)
Abstract: Choosing the right learning model during the learning process is a very important thing for a teacher to do, to increase student learning activities. This research aims to find out the influence of learning model the Contextual Teaching and Learning toward student learning activities on biodiversity material in class X SMA Negeri 1 Luwuk. This research is a quasi-experimental research with a Nonequivalent Control Group Design research design. The population of the research was class X students of SMA Negeri 1 Luwuk for the 2022/2023 school year. The samples of this research were class Xb as an experimental class and class Xe as a control class, each of which consists of 39 students. The data collection technique was used students learning activity sheets with 8 aspects of assessment, namely observing teacher lessons, expressing questions, doing group assignments, listening to discussion group friends’ conversations, solving problems, presenting group assignments, answering questions, and approve and receiving opinions. The data were analyzed using a normality test and a t-test with the help of an SPSS application. The results of this research showed that there was an influence of learning model the Contextual Teaching and Learning on student learning activities on biodiversity material in class X SMA Negeri 1 Luwuk with a calculated tcount = 5.470 ˃ ttable = 1.665 and a significant value of 0.000 ˂ 0.05. Keywords: Learning Activities, Contextual Teaching and Learning